SOCIAL DETERMINANTS AND SKIN CANCER: AN ESSENTIAL APPROACH TO PRESERVE PUBLIC HEALTH (International Seven Journal of Health Research, 2024)
Cancer, being the second leading cause of death globally, represents a significant challenge for public health (Ferlay et al., 2021). With the rising life expectancy and lifestyle habits of contemporary society, the increase in chronic diseases, including cancer, becomes evident. This chapter explores skin cancer, one of the most prevalent types in Brazil and worldwide, highlighting not only its pathophysiological complexity but also the access barriers that impact the patient's journey. The Brazilian scenario, marked by inequalities and social determinants, reveals the importance of public policies and prevention strategies to face the challenges associated with the diagnosis and treatment of skin cancer.